The Effect of Shared Reading Strategy Using Digital Photo Story and Achievement Motivation on Students’ Reading Comprehension - ., LUH PUTU DIAN KRESNAWATI; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Dr.Ni Made Ratminingsih, MA (Universitas Pendidikan Ganesha, 2013)
Penelitian ini adalah penelitian eksperimen yang bertujuan untuk mengetahui perbedaan pemahaman membaca bagi siswa yang diajar dengan shared reading yang dipadu dengan digital photo story dan siswa yang diajar dengan menggunakan strategi konvensional, dengan mempertimbangkan motivasi pencapaina siswa di SMP Negeri 6 Singaraja tahun ajaran 2012/2013. Terdapat 2 variabel tidak terikat (Strategi shared reading dengan menggunakan digital photo story dan motivasi berprestasi) dan satu variabel terikat (pemahaman membaca). Data yang telah terkumpul dianalisis dengan menggunakan ANOVA dua jalur dan tes Tukey. Hasilnya menunjukkan: (1) adanya perbedaan pemahaman membaca siswa yang signifikan antara siswa yang diajarkan dengan menggunakan stategi shared reading dengan digital photo story dan mereka yang diajarkan dengan strategi konvensional, (2) adanya dampak interaksi yang signifikan antara strategi shared reading dengan menggunakan digital photo story dengan motivasi pencapaian siswa dalam pemahaman membaca, (3) adanya perbedaan yang signifikan dalam pemahaman membaca siswa antara siswa yang memiliki motivasi berprestasi tinggi ketika mereka diajar dengan menggunakan strategi shared reading dengan digital photo story dan strategi konvensional, dan (4) adanya perbedaan yang signifikan dalam pemahaman membaca siswa yang memiliki motivasi berprestasi rendah ketika mereka diajar dengan strategi shared reading dengan digital photo story dan strategi konvensional.Kata Kunci : Pemahaman membaca, strategi shared reading, digital photo story, motivasi pencapaian The main purpose of this study is to know the effect of shared reading strategy using digital photo story and achievement motivation on students? reading comprehension. This study was conducted at SMP Negeri 6 Singaraja, specifically on the seventh grade students of the academic year 2012/2013. There were two independent variables (Shared reading strategy using digital photo story and achievement motivation) and one dependent variable (reading comprehension). The data were analyzed using two-way ANOVA and Tukey Test. The results showed that: (1) there was a significant difference on students? reading comprehension between students who were taught by shared reading strategy using digital photo story and conventional reading strategy, and (2) there was a significant interactional effect between shared reading strategy using digital photo story and students? achievement motivation on reading comprehension, (3) there was a significant difference between the students? reading comprehension achievement of the students with high achievement motivation when they are taught by shared reading strategy using digital photo story and conventional reading strategy, and (4) there was a significant difference between the students? reading comprehension achievement of the students with low achievement motivation when they are taught by shared reading strategy using digital photo story and conventional reading strategy.keyword : Reading comprehension, shared reading, digital photo story, achievement motivation